Exposición a arsénico en agua potable, metabolismo, y sus efectos sobre los resultados perinatales en Tacna, Perú - Fano Sizgorich, Diego Alejandro (2021)
Introduction: It is estimated that about 140 million people worldwide are exposed to arsenic levels in drinking water above the WHO's suggested limit of 10 μg/L. Exposure during pregnancy has been associated with low birth weight, preterm birth, small for gestational age (SGA), etc. In Peru, the province of Tacna has shown considerable concentrations of arsenic in drinking water. Objective: The aim of this study is to assess the effect of arsenic consumption in drinking water on perinatal outcomes in Tacna province. Methods: A longitudinal observational study was carried out in which 150 pregnant women were recruited up to the 24th week of pregnancy. A drinking water sample from their most consumed source was collected for the analysis of total inorganic arsenic, and a urine sample for the evaluation of total urinary arsenic and its different metabolites (U-iAsIII, U-iAsV, arsenobetaine, U-MMA and U-DMA). Perinatal records (birth weight, birth height and gestational age) were obtained from the clinical records of the Hipólito Unanue Hospital in Tacna. Linear and logistic regression analyses were performed to evaluate the association between urinary arsenic concentrations and its metabolites with perinatal results. Models were evaluated for multicollinearity and goodness-of-fit. Results: About 66% of pregnant women were exposed to arsenic concentrations in drinking water ≥25 μg/L, the level of exposure was dependent on the housing district, with the southern area showing the lowest concentration. The average concentration of total arsenic in urine was 46.10 μg/L, with the northern zone showing the highest concentration (56.02 μg/L, p<0.05); while for the metabolite DMA, the metropolitan zone showed the highest concentration (17.69 μg/L, p<0.05). The average birth weight was 3618 g. The prevalence of premature birth, PEG and large for gestational age (GEG) was 3.75%, 4.38% and 29.38%, respectively, with the lowest prevalence of GEG in the metropolitan area (18.97%), and the highest in the northern area (40%) (p=0.01). A statistically significant association was found between the upper quartile of U-iAsIII and birth weight (β-coef: 232.93 g, 95%IC 5.91 - 459.95). It was observed an apparent, although not statistically significant, trend of higher incidence of premature birth with a higher concentration of U-tAs and the different metabolites, except for arsenobetaine and DMA. Conclusion: The northern and central areas of Tacna showed the highest values of arsenic in water consumption by pregnant women, also reflected in urine; also, in the central area was the lowest incidence of GEG. The absence of association of arsenic on PEG may be due to some polymorphism due to generational age of exposure to arsenic or to the Aymara ancestry of the population.